2021
DOI: 10.1001/jamasurg.2020.7081
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Survival Outcomes of Hybrid Minimally Invasive Esophagectomy in Esophageal Cancer

Abstract: for the Fédération de Recherche en Chirurgie (FRENCH) and French Eso-Gastric Tumors (FREGAT) Working Groups IMPORTANCE Available data comparing the long-term results of hybrid minimally invasive esophagectomy (HMIE) with that of open esophagectomy are conflicting, with similar or even better results reported for the minimally invasive esophagectomy group. OBJECTIVE To evaluate the long-term, 5-year outcomes of HMIE vs open esophagectomy, including overall survival (OS), disease-free survival (DFS), and patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 42 publications
0
47
0
1
Order By: Relevance
“…Instead, it found that major intraoperative and postoperative complications, as well as major pulmonary complications, negatively affected OS and DFS on multivariable analysis. 62 In this study, we found that RAMIE was associated with a modest decrease in pulmonary complications compared with VAMIE. Accordingly, it is plausible that RAMIE may be associated with improved long-term oncologic outcomes.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Instead, it found that major intraoperative and postoperative complications, as well as major pulmonary complications, negatively affected OS and DFS on multivariable analysis. 62 In this study, we found that RAMIE was associated with a modest decrease in pulmonary complications compared with VAMIE. Accordingly, it is plausible that RAMIE may be associated with improved long-term oncologic outcomes.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, the 5-year follow-up analysis of the Minimally Invasive vs Open Esophageal Resection trial 62 found no difference in long-term oncologic outcomes between patients who underwent a hybrid esophagectomy (laparoscopy and thoracotomy) and open transthoracic esophagectomy. Instead, it found that major intraoperative and postoperative complications, as well as major pulmonary complications, negatively affected OS and DFS on multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the new era of minimally invasive laparoscopic surgery, minimally invasive esophagectomy started to be performed in the 2000s, providing the well-known advantages on recovery of the minimally invasive procedures. Safety and efficacy of minimally invasive esophagectomy has been reported in several experiences [ 4 , 5 , 6 , 7 ], further providing similar oncologic results and long term recurrence rate [ 8 , 9 , 10 ]. However, on a clinical point of view, the introduction of minimally invasive esophagectomy in the clinical practice is far to be considered as a standard of care.…”
Section: Introductionmentioning
confidence: 80%
“…[9][10][11][12][13][14] However, because a totally minimally invasive transthoracic esophagectomy is a challenging and demanding procedure, some esophageal surgeons still perform open (OE) or hybrid esophagectomy (HE). [15][16][17][18][19][20] The aim of this systematic review and meta-analysis was to compare surgical outcomes between OE, HE, and totally minimally invasive Ivor Lewis esophagectomy (TMIE).…”
Section: Perspectivementioning
confidence: 99%